Smart City Development in the New Capital City: Indonesian Government Plans - Rifaid Rifaid; Abdurrahman Abdurrahman; Tawakkal Baharuddin; Bayu Mitra A. Kusuma (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2023)
The idea of a smart city and a new capital city in Indonesia is complex, so planning and the government's role are crucial. The purpose of this research is based on two big questions about the government's plan for preparing for development and the potential for smart city development in the new capital city. This study was done based on the results of a direct examination of official government documents using a thematic analysis approach and an analytical tool called Nvivo 12 Plus. This research was able to show what the Indonesian government's plans are and what they could do to build smart cities in the new capital city (IKN/Nusantara). The findings of this study map out six smart city support systems, which are the government's priority plans, including urban systems, safety and security, livability and urban life, government services, the environment and sustainability, and access and mobility. They all focus on technology adaptation, digitization, renewable energy, and sustainability. Despite these priority plans, there are still significant challenges to rethinking the prospects and potential for developing smart cities in the new capital city, especially the issues of human resources, budget capacity, infrastructure, and government bureaucratic adaptation patterns. This study proposes to set up a smart governance system to adapt to the new system, primarily to accommodate those problems and challenges. It can contribute to unravelling smart cities' complexities, challenges, and future development potential.